Medieval cognitive system (The Impact of Greek Discourse on Christian Philosophy) - M.D. Mohamed Hato Aziz (Zien Journals, 2022)
This research shows how Christian philosophy in the Middle Ages was confronted with the Greek discourse. Christian philosophy is based on belief, revelation, and receiving revelation commands from Christ. As for Greek philosophy, it represents a strange woodcutter within the Christian knowledge, because its origin is ethnic, believing in the plurality of gods. Certainly, the cognitive rules of Greece differ in this case from the Christian rules, and we noticed during the research and review of the history of the meeting between the two systems - Christianity and Greek - that Christian philosophy received the Greek discourse with great caution, and dealt with it, by applying measures of prevention, such as exclusion, and prohibition And the determinants of the fear of the spread of Greek discourse that poses a threat to Christian philosophy, and by applying these procedures, Christian philosophy established a Christian Greek discourse in contrast to the purely Greek discourse
Keywords: Greek philosophy; medieval; christianity